Sensitivity of Lyme Borreliosis Spirochetes to Serum Complement of Regular Zoo Animals: Potential Reservoir Competence of Some Exotic Vertebrates - Ticha, Lucie; Golovchenko, Maryna; Oliver, James H; Grubhoffer, Libor; Rudenko, Nataliia (Vector borne and zoonotic diseases (Larchmont, N.Y.), 2016)
Reaction of vertebrate serum complement with different Borrelia burgdorferi sensu lato species is used as a basis in determining reservoir hosts among domesticated and wild animals. Borrelia burgdorferi sensu stricto, Borrelia garinii, and Borrelia afzelii were tested for their sensitivity to sera of exotic vertebrate species housed in five zoos located in the Czech Republic. We confirmed that different Borrelia species have different sensitivity to host serum. We found that tolerance to Borrelia infection possessed by hosts might differ among individuals of the same genera or species and is not affected by host age or sex. Of all zoo animals included in our study, carnivores demonstrated the highest apparent reservoir competency for Lyme borreliosis spirochetes. We showed that selected exotic ungulate species are tolerant to Borrelia infection. For the first time we showed the high tolerance of Siamese crocodile to Borrelia as compared to the other studied reptile species. While exotic vertebrates present a limited risk to the European human population as reservoirs for the causative agents of Lyme borreliosis, cases of incidental spillover infection could lead to successful replication of the pathogens in a new host, changing the status of selected exotic species and their role in pathogen emergence or maintenance. The question if being tolerant to pathogen means to be a competent reservoir host still needs an answer, simply because the majority of exotic animals might never be exposed to spirochetes in their natural environment.
Keywords: Male; Borrelia burgdorferi; lymeská nemoc; Serum complement; zdroje nemoci; Lyme Disease; Zoo; Animals, Zoo; mužské pohlaví; komplement; Exotic animals; Complement System Proteins; Animals; zvířata v ZOO; Vertebrates; Borrelia burgdorferi sensu lato; ženské pohlaví; Reservoir hosts; zvířata; Disease Reservoirs; Female; obratlovci; Lyme disease